Public debt and economic growth in Euro area countries. A wavelet approach - Albu, Ada-Cristina; Albu, Lucian-Liviu (Technological and Economic Development of Economy, 2021)
In this paper we propose to analyze the dynamic of the relation between public debt and economic growth rate for Euro area countries by employing a wavelet approach, establishing thus both short-term and long-term correlations between these two variables. In this way we will present time-frequency dependencies between debt and economic growth and differentiate between short term and long-term effects. High levels of public debt have a negative impact on the economic output, because they entail concerns about debt sustainability. Non-linear analysis of the debt-growth nexus shows the existence of thresholds from which rising indebtedness can hamper economic growth. Using wavelet analysis, we demonstrate that there is a strong relation between public debt and economic growth, especially for high frequencies, public debt having a significant impact on economic growth in case of periods situated above 2 years for most Euro Zone member states. High debt levels can cause serious effects on fiscal stability and therefore require fiscal consolidation in order to restore economic growth. Therefore, Euro Zone member states should implement prudent debt policies and establish clear limits for debt increase, in order to comply with fiscal sustainability and ensure conditions for preserving economic growth. First published online 08 February 2021